(untitled) (Al-Qamar, 2021)
Muslim consumers are very similar to any other consumer segments, demanding Halal, healthy and quality products, which must conform to Sharīʻah requirements. This large market has created interest from food producer’s worldwide including Muslim and non-Muslim countries. Multinational firms acknowledged the significance of Halal in sustaining competitiveness. Halal certificate can play an important role to assure consumers that this product has got the necessary conditions of Halal product. The present study was carried out with a concept of Halal unification for food production and processing companies and certification process for CBs working in Halal certification of different products as well as processed for stakeholders considering the major requirements of 4 selected standards prepared by Pakistan, Malaysia, SMIIC and GSO countries.